Optimization method for hole transport layer interface modification and application thereof
By modifying the interface of the hole transport layer with organic materials, the problems of composite loss, interface contact and stability in inverted perovskite solar cells are solved, and the film-forming properties and device performance of perovskite film are improved.
Patent Information
- Application Number
- CN202510087004.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
Inverted perovskite solar cells have problems with composite loss, interface contact and stability, mainly due to poor contact and defects between the hole transport layer and the perovskite layer.
The interface modification of the hole transport layer is used to modify the hole transport layer interfacially by using organic materials such as cinnamon alcohol, citronellol or phenylethanol, and the contact quality of the hole transport layer and the perovskite layer is improved through deployment and heat treatment.
It significantly improves the film-forming properties of perovskite films and the overall performance and stability of the device, reducing compound losses and interface energy losses.
Smart Images

Figure CN119907607A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cell materials, and in particular to an optimization method for interface modification of a hole transport layer and application thereof. Background Art
[0002] Energy crisis and environmental problems are the two major dilemmas facing mankind today. Solar energy is highly favored because it is clean, pollution-free and has huge reserves. The current mainstream silicon-based solar cells in the market cannot achieve large-scale application of solar energy due to their high cost and brittleness. Perovskite solar cells are considered to be the most promising photovoltaic cells for large-scale application due to their high efficiency and low-temperature preparation. Perovskite solar cells mainly have two configurations - upright and inverted structures. Compared with other device configurations, inverted perovskite solar cells have unique advantages such as low-temperature preparation, high power density, and compatibility with flexibility. They have unique application potential in the fields of ultra-light electronic devices and wearable electronic devices. In addition, this type of device has the potential to be more stable because it can avoid the use of a hole transport layer 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-MeOTAD), thereby avoiding the use of (fluorosulfonyl imide) lithium (LiFSI) and 4-tert-butylpyridine (TBP) hygroscopic dopants.
[0003] However, inverted perovskite solar cells have more serious problems with recombination loss, interface contact and stability. These recombination loss and stability problems mainly come from: First, during the low-temperature preparation of organic-inorganic hybrid perovskite polycrystalline films, due to the fast crystallization rate and complex solvent atmosphere, a large number of defects are formed at the grain boundaries and crystal planes, thereby forming recombination centers and causing recombination losses. Second, the undesirable hole transport layer / perovskite interface contact causes incomplete perovskite coverage to produce holes, leading to serious interface energy loss and poor device performance and stability. Third, the inherent properties of the hole transport layer. Due to the hydrophobicity of the hole transport layer and the lack of adhesion to the perovskite layer, the perovskite film has poor film quality and many defects, affecting the performance of perovskite solar cells. Fourth, element diffusion. Due to the poor film-forming properties of fullerenes, the inverted device has insufficient blocking ability for interlayer element diffusion, which is prone to adverse behaviors such as electrode corrosion and metal diffusion, resulting in increased recombination losses.
[0004] In the prior art, the common methods for dealing with the recombination loss and stability problems of inverted perovskite solar cells include the following three categories:
[0005] (1) Crystallization regulation: Starting from perovskite grains, develop single-crystal perovskite solar cells, or use atmosphere / solvent annealing, crystallization control and chemical engineering to increase the size of polycrystalline perovskite crystals and reduce grain boundaries and surface defects (Nat. Commun., 2015, 6, 7586.; Nat. Commun., 2017, 8, 1890; Adv. Mater., 2014, 26, 6503-6509; Adv. Energy Mater., 2022, 12, 2201787).
[0006] (2) Defect passivation: Defects on the surface and grain boundaries of perovskite films are passivated using passivation materials. Many materials have been used as passivators, such as organic small molecules, polymers, ammonium salts, ionic liquids, insulating materials, etc.
[0007] (3) The hole transport layer interface modification strategy is widely used to overcome interface problems; many materials, such as aluminum oxide and polyethylene oxide (PEO), are intercalated into the interlayer of the inverted perovskite device to improve the hydrophobicity of the hole transport layer, improve the film-forming properties of the perovskite layer, enhance the interlayer contact, and inhibit the generation of holes.
[0008] In the study of perovskite photovoltaic devices, the interface modification strategy of the hole transport layer is considered to be one of the key technologies to improve the performance and stability of the device. As the basis of perovskite crystallization, the properties of the hole transport layer directly affect the quality of perovskite crystallization. In addition, the interface problem between the hole transport layer and the perovskite is also the main factor limiting the performance and stability of the device, such as poor physical contact and the mismatch between the surface energy of the perovskite precursor and the hole transport layer. In particular, the mismatch between the hydrophobic hole transport layer and the perovskite precursor seriously affects the repeatability and reliability of the device. Therefore, by effectively modifying the hole transport layer, not only the overall quality of the perovskite film can be improved, but also the contact performance of the bottom interface, the quality of the perovskite film, and the preparation repeatability and reliability of the device can be enhanced, which is crucial for the practical application of perovskite photovoltaic technology.
[0009] However, the current technological development is limited by material costs, solvent toxicity, method versatility and industrial production requirements, and lacks efficient, low-cost and environmentally friendly hole transport layer modification solutions. Therefore, the development of new efficient, economical and environmentally friendly hole transport layer optimization methods is of great significance to promote the industrialization of perovskite photovoltaic technology.
[0010] Based on this, it is of great practical significance to provide an optimization method for interface modification of the hole transport layer. Summary of the invention
[0011] The purpose of the present invention is to provide an optimization method for hole transport layer interface modification and its application, so as to solve the problems existing in the above-mentioned prior art, to achieve a comprehensive improvement in the contact quality of the perovskite film and the hole transport layer / perovskite interface in the perovskite device, to achieve improved film forming properties of the perovskite, and thus to improve the composite loss and stability problems caused by film forming properties and interface contact factors.
[0012] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0013] The present invention provides an optimization method for interface modification of a hole transport layer, comprising the following steps:
[0014] Performing a development treatment on the hole transport layer using an organic material to obtain a treated hole transport layer;
[0015] performing heat treatment on the treated hole transport layer;
[0016] The organic material comprises one or more of a cinnamyl alcohol solution, a citronellol solution and a phenylethanol solution.
[0017] Further, the material of the hole transport layer is one or more of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(3-hexylthiophene-2,5-diyl), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid (MeO-2PACz), polyethylenedioxythiophene-poly(styrenesulfonate), metal oxide and graphene oxide, wherein the metal oxide is one or more of vanadium oxide, nickel oxide, tungsten oxide and molybdenum oxide.
[0018] Furthermore, the solvent of the organic material is one of isopropanol, ethanol and butanol, and the concentration of the solvent is 1-20 mg / mL.
[0019] Furthermore, the unfolding treatment is one of spray coating, blade coating, spin coating, slit coating, roll-to-roll coating, immersion coating and pull coating.
[0020] Furthermore, the heat treatment method is specifically one of hot plate heating, laser heating, baking heating, hot air heating and microwave heating, the heat treatment time is 5 to 30 minutes, and the temperature is 50 to 100°C.
[0021] The present invention also provides a hole transport layer material modified by the optimized method for modifying the hole transport layer interface described in the above technical solution.
[0022] The present invention also provides an application of the hole transport layer material described in the above technical solution in an inverted perovskite solar cell, comprising the following steps:
[0023] forming a hole transport layer on a transparent conductive substrate;
[0024] The hole transport layer is modified at the interface by using the optimization method for modifying the interface of the hole transport layer as described in any one of claims 1 to 5 to obtain a modified hole transport layer;
[0025] A perovskite layer is fabricated on the modified hole transport layer.
[0026] Furthermore, the specific process of making the hole transport layer is: spin coating the hole transport layer on the transparent conductive substrate, and then performing heat treatment to obtain the hole transport layer; the specific process of making the perovskite layer is: spin coating an electron transport material with a thickness of 10-50nm on the hole transport layer, heat treating it at 80-100°C for 10-60 minutes to form an electron transport layer, and then spin coating a cathode interface modification layer with a thickness of 5-10nm and evaporating a metal electrode with a thickness of 100-200nm.
[0027] Furthermore, the thickness of the hole transport layer is 10 to 100 nm, and the temperature of the heat treatment for making the hole transport layer is 60 to 100° C., and the time is 10 to 30 minutes.
[0028] Furthermore, the transparent conductive substrate is a tin oxide or a nanowire; wherein the tin oxide is a fluorine-doped tin oxide or an indium-doped tin oxide; the nanowire is any one of an activated carbon fiber fabric, a silver nanowire and a copper nanowire; the structure of the perovskite layer is specifically MAPbI3 or FAPbI3 or (Cs 0.05 (FA 0.83 MA 0.17 ) 0.95 Pb(I 0.85 Br 0.15 )3; the electron transport layer material is one or more of fullerene derivatives and non-fullerene derivatives; the cathode interface modification material is one or more of bathocuproin, C60, and titanium dioxide; the material of the metal electrode is any one of gold, silver, aluminum and copper.
[0029] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0030] The present invention proposes an optimization method for interface modification of the hole transport layer and its practical application. The modified materials used include cinnamyl alcohol, citronellol or phenylethyl alcohol. These materials have the advantages of economy, environmental protection and non-toxicity, and can be dissolved in alcohol solvents. They are suitable for large-area modification by simple methods such as spraying, thereby realizing cheap and non-destructive treatment of the hole transport layer. At the same time, these modified materials are used to improve the surface properties of the hole transport layer. With the synergistic effect of polar and non-polar functional groups, a hinge effect can be formed between the hole transport layer and the perovskite precursor, thereby regulating the crystallization process of the perovskite and improving the interface contact, thereby improving the overall performance and stability of the device. In addition, through the polarity difference of the molecular functional groups, orderly molecular assembly is achieved, the interface electric field is constructed, and the carrier transport dynamics of the device anode interface are regulated to enhance the performance of the device. This innovative method not only makes the modification process more efficient and environmentally friendly, but also significantly improves the stability of the device and its operating performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The structure of the inverted perovskite solar cell prepared in Example 1 of the present invention and the processing mechanism diagram based on cinnamyl alcohol (CA) material;
[0032] Figure 2 The water contact angle diagram of the anode interface before and after treatment of the present invention;
[0033] Figure 3 This is a SEM comparison of the surface of the untreated and treated perovskite film of the present invention;
[0034] Figure 4 JV curves of the perovskite solar cells of Comparative Example 1 and Example 1 of the present invention;
[0035] Figure 5 Schematic diagram of the stability of the perovskite solar cells of Comparative Example 1 and Example 1 of the present invention at 85 degrees Celsius. DETAILED DESCRIPTION
[0036] The present invention provides an optimization method for interface modification of a hole transport layer, comprising the following steps:
[0037] Performing a development treatment on the hole transport layer using an organic material to obtain a treated hole transport layer;
[0038] performing heat treatment on the treated hole transport layer;
[0039] The organic material comprises one or more of a cinnamyl alcohol solution, a citronellol solution and a phenylethanol solution.
[0040] In the present invention, the material of the hole transport layer is one or more of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(3-hexylthiophene-2,5-diyl), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid (MeO-2PACz), polyethylenedioxythiophene-poly(styrenesulfonate), metal oxide and graphene oxide, wherein the metal oxide is one or more of vanadium oxide, nickel oxide, tungsten oxide and molybdenum oxide.
[0041] In the present invention, the solvent of the organic material is one of isopropanol, ethanol and butanol, and the concentration of the solvent is 1-20 mg / mL.
[0042] In the present invention, the unwinding treatment is one of spray coating, blade coating, spin coating, slit coating, roll-to-roll coating, immersion coating and pull coating.
[0043] In the present invention, the heat treatment method is specifically one of hot stage heating, laser heating, baking heating, hot air heating and microwave heating. The heat treatment time is 5 to 30 minutes and the temperature is 50 to 100°C, and more preferably 5 to 20 minutes and the temperature is 50 to 80°C.
[0044] The present invention also provides a hole transport layer material modified by the optimized method for modifying the hole transport layer interface described in the above technical solution.
[0045] The present invention also provides an application of the hole transport layer material described in the above technical solution in an inverted perovskite solar cell, comprising the following steps:
[0046] forming a hole transport layer on a transparent conductive substrate;
[0047] The hole transport layer is modified at the interface by using the optimization method for modifying the interface of the hole transport layer as described in any one of claims 1 to 5 to obtain a modified hole transport layer;
[0048] A perovskite layer is fabricated on the modified hole transport layer.
[0049] In the present invention, the specific process of making the hole transport layer is: spin coating the hole transport layer on the transparent conductive substrate, and then heat treating to obtain the hole transport layer; the specific process of making the perovskite layer is preferably: spin coating an electron transport material with a thickness of 10-50nm on the hole transport layer, heat treating at 80-100°C for 10-60 minutes to form an electron transport layer, and then spin coating a cathode interface modification layer with a thickness of 5-10nm and vapor-depositing a metal electrode with a thickness of 100-200nm, and further preferably spin coating an electron transport material with a thickness of 10-30nm on the hole transport layer, heat treating at 80-90°C for 20-40 minutes to form an electron transport layer, and then spin coating a cathode interface modification layer with a thickness of 5-8nm and vapor-depositing a metal electrode with a thickness of 100-150nm.
[0050] In the present invention, the thickness of the hole transport layer is 10-100 nm, and the temperature of the heat treatment for making the hole transport layer is 60-100° C. and the time is 10-30 minutes.
[0051] In the present invention, the transparent conductive substrate is tin oxide or nanowire; wherein the tin oxide is fluorine-doped tin oxide or indium-doped tin oxide; the nanowire is any one of activated carbon fiber fabric, silver nanowire and copper nanowire; the structure of the perovskite layer is specifically MAPbI3 or FAPbI3 or Cs 0.05 (FA 0.83 MA 0.17 ) 0.95 Pb(I 0.85 Br 0.15 )3 or Rb 0.05 Cs 0.05 MA 0.05 FA 0.85 Pb[I 0.95 Br 0.05 ]3; the electron transport layer material is one or more of fullerene derivatives and non-fullerene derivatives; the cathode interface modification material is bathocuproin, C 60 , titanium dioxide or more; the material of the metal electrode is any one of gold, silver, aluminum and copper.
[0052] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1
[0055] (1) Spin-coating a 10 nm thick poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) on a transparent conductive substrate as a hole transport layer and heat treating the layer at 100°C for 10 minutes;
[0056] (2) spin coating a cinnamyl alcohol (CA) material with a thickness of 5-10 nm on the hole transport layer described in step (1), and treating at a temperature of 60° C. for 5 minutes;
[0057] (3) Spin-coating a 450 nm thick perovskite thin film material (Cs 0.05 (FA 0.83 MA 0.17 ) 0.95 Pb(I 0.85 Br 0.15 )3), heat treatment at 100°C for 60 minutes to form a perovskite layer;
[0058] (4) spin coating a fullerene derivative with a thickness of 30 nm as an electron transport material on the perovskite layer prepared in step (3), and heat treating the layer at 90° C. for 30 minutes to form an electron transport layer;
[0059] (5) Spin-coating a 10 nm thick bathocuproin (BCP) on the electron transport layer prepared in step (4) as a cathode interface modification layer without heat treatment;
[0060] (6) Silver with a thickness of 100 nm is evaporated on the thin film prepared in step (5) as a metal electrode.
[0061] Comparative Example 1
[0062] (1) spin coating a hole transport layer with a thickness of 10 nm on a transparent conductive substrate, and heat treating the layer at 100° C. for 10 minutes, wherein the transparent substrate is indium-doped tin oxide (ITO) and the hole transport layer is poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA);
[0063] (2) Spin-coat the hole transport layer modification layer in step (1) with a thickness of 450 nm of the blended perovskite Cs 0.05 (FA 0.83 MA 0.17 ) 0.95 Pb(I 0.85 Br 0.15 )3, heat treatment at 100°C for 60 minutes to form a perovskite layer;
[0064] (3) Spin-coat a fullerene derivative (PC) with a thickness of 30 nm on the perovskite layer prepared in step (2). 61BM), heat treated at 90°C for 30 minutes to form an electron transport layer;
[0065] (4) spin coating 10 nm of bathocuproin (BCP) on the electron transport layer prepared in step (3) as a cathode interface modification layer without heat treatment;
[0066] (5) Silver was vacuum-deposited on the hole transport layer / perovskite / fullerene electron transport layer / bathocuproine (BCP) treated in step (4) to form a metal electrode with a thickness of 100 nm.
[0067] Example 2
[0068] (1) spin coating a hole transport layer with a thickness of 10 nm on a transparent conductive substrate, and heat treating it at 80° C. for 20 minutes, wherein the transparent substrate is indium-doped tin oxide (ITO), and the hole transport layer is polyvinyl carbazole and poly (3-hexylthiophene-2,5-diyl);
[0069] (2) spin coating a cinnamyl alcohol (CA) modification layer with a thickness of 50 nm on the hole transport layer described in step (1), and heat treating at 60° C. for 5 minutes;
[0070] (3) spin coating methylamine lead iodide (MAPbI3) with a thickness of 0.3 μm on the hole transport layer modification layer in step (2), and heat treating at 100° C. for 30 minutes to form a perovskite layer;
[0071] (4) Spin-coat a fullerene derivative (PC) with a thickness of 10 nm on the perovskite layer prepared in step (3). 61 BM), heat treated at 80°C for 30 minutes to form an electron transport layer;
[0072] (5) Spin-coat a 40 nm thick bathocuproine (BCP) cathode interface modification layer onto the fullerene electron transport layer prepared in step (4).
[0073] (6) Vacuum-evaporating silver (Au) on the hole transport layer / perovskite / fullerene / bathocuproine treated in step (5) to form a metal electrode with a thickness of 150 nm.
[0074] Example 3
[0075] (1) A hole transport layer with a thickness of 20 nm was spin-coated on a transparent conductive substrate and heat treated at 100° C. for 10 minutes, wherein the transparent substrate was indium-doped tin oxide (ITO) and the hole transport layer was nickel oxide (NiO x );
[0076] (2) spin coating a cinnamyl alcohol (CA) modification layer with a thickness of 50 nm on the hole transport layer described in step (1), and heat treating at 60° C. for 5 minutes;
[0077] (3) spin coating formamidinium lead iodide (FAPbI3) with a thickness of 0.3 μm on the hole transport layer in step (2), and heat treating at 100° C. for 30 minutes to form a perovskite layer;
[0078] (4) Spin-coat a fullerene derivative (PC) with a thickness of 10 nm on the perovskite layer prepared in step (3). 61 BM), heat treated at 80°C for 50 minutes to form an electron transport layer;
[0079] (5) Spin-coat bathocuproine (BCP) with a thickness of 7 nm on the electron transport layer prepared in step (4).
[0080] (6) Silver (Ag) is vacuum-deposited on the thin film treated in step (5) to form a metal electrode with a thickness of 100 nm.
[0081] Example 4
[0082] (1) spin coating a hole transport layer with a thickness of 30 nm on a transparent conductive substrate, and heat treating the layer at 100° C. for 10 minutes, wherein the transparent substrate is indium-doped tin oxide (ITO), and the hole transport layer is [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid (MeO-2PACz);
[0083] (2) spin coating a cinnamyl alcohol (CA) modification layer with a thickness of 50 nm on the hole transport layer described in step (1), and heat treating at 60° C. for 5 minutes;
[0084] (3) Spin coating a 400 nm thick blended perovskite (Rb0.05Cs0.05MA0.05FA0.85Pb[I0.95Br0.05]3) on the hole transport layer in step (2), and heat treating at 100° C. for 30 minutes to form a perovskite layer;
[0085] (4) Spin-coat a fullerene derivative (PC) with a thickness of 20 nm on the perovskite layer prepared in step (3). 71 BM), heat treated at 80°C for 50 minutes to form an electron transport layer;
[0086] (5) Spin-coat 2,4-diamino-6,7-diisopropylpteridine phosphate (DPP) with a thickness of 7 nm on the electron transport layer prepared in step (4).
[0087] (6) Silver (Ag) is vacuum-evaporated on the organic-inorganic hybrid perovskite / fullerene surface heterojunction treated in step (5) to form a metal electrode with a thickness of 100 nm.
[0088] Experiments were conducted on Examples 1 to 4 and Comparative Example 1. The results are as follows: Figure 1 to Figure 5 As shown:
[0089] like Figure 1 Shown is the structure of the inverted perovskite solar cell prepared in Comparative Example 1 and a mechanism diagram of modification with cinnamyl alcohol (CA).
[0090] like Figure 2 As shown, the water contact diagram of the anode interface film with or without cinnamyl alcohol (CA) modification prepared by the method in Comparative Example 1 and Example 1 is shown, based on Figure 2 It can be seen that the hydrophobicity of the film modified with cinnamyl alcohol (CA) was effectively improved.
[0091] like Figure 3 As shown, it is a SEM comparison of the surface of the anode interface film with or without cinnamyl alcohol (CA) modification prepared by the method of comparative example 1 and example 1, based on Figure 3 It can be seen that the film modified with cinnamyl alcohol (CA) is denser and more uniform;
[0092] like Figure 4 As shown, it is a comparison diagram of the JV curves of the perovskite solar cells prepared in Example 1 of the present invention and Comparative Example 1, based on Figure 4 It can be seen that the performance parameters of the modified device are significantly improved, and the specific data are shown in Table 1;
[0093] Table 1 JV curve data of perovskite solar cells prepared in Example 1 and Comparative Example 1
[0094]
[0095]
[0096] like Figure 5 FIG. 1 is a schematic diagram of the stability of a perovskite solar cell at 85 degrees Celsius according to an embodiment of the present invention. The comparison shows that the stability of the device modified with cinnamyl alcohol (CA) is significantly improved.
[0097] The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The above examples are only used to help understand the method and core ideas of the present invention. At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for optimizing the interface modification of a hole transport layer, characterized in that: The following steps are involved: Performing a development treatment on the hole transport layer using an organic material to obtain a treated hole transport layer; performing heat treatment on the treated hole transport layer; The organic material comprises one or more of a cinnamyl alcohol solution, a citronellol solution and a phenylethanol solution.
2. The optimization method for hole transport layer interface modification according to claim 1, characterized in that: The material of the hole transport layer is one or more of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(3-hexylthiophene-2,5-diyl), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid (MeO-2PACz), polyethylenedioxythiophene-poly(styrenesulfonate), metal oxide and graphene oxide, wherein the metal oxide is one or more of vanadium oxide, nickel oxide, tungsten oxide and molybdenum oxide.
3. The optimization method for hole transport layer interface modification according to claim 1, characterized in that: The solvent of the organic material is one of isopropanol, ethanol and butanol, and the concentration of the solvent is 1-20 mg / mL.
4. The optimization method for hole transport layer interface modification according to claim 1, characterized in that: The unwinding process is one of spray coating, blade coating, spin coating, slit coating, roll-to-roll coating, dip coating and pull coating.
5. The optimization method for hole transport layer interface modification according to claim 1, characterized in that: The heat treatment method is specifically one of hot plate heating, laser heating, baking heating, hot air heating and microwave heating. The heat treatment time is 5 to 30 minutes and the temperature is 50 to 100°C.
6. A hole transport layer material modified by the optimization method for hole transport layer interface modification as claimed in any one of claims 1 to 5.
7. Application of the hole transport layer material according to claim 6 in an inverted perovskite solar cell, characterized in that: The following steps are involved: forming a hole transport layer on a transparent conductive substrate; The hole transport layer is modified at the interface by using the optimization method for modifying the interface of the hole transport layer as described in any one of claims 1 to 5 to obtain a modified hole transport layer; A perovskite layer is fabricated on the modified hole transport layer.
8. The use according to claim 7, characterized in that: The specific process of making the hole transport layer is: spin coating the hole transport layer on the transparent conductive substrate, and then heat treating to obtain the hole transport layer; the specific process of making the perovskite layer is: spin coating the electron transport material with a thickness of 10-50nm on the hole transport layer, heat treating at 80-100°C for 10-60 minutes to form an electron transport layer, and then spin coating a cathode interface modification layer with a thickness of 5-10nm and vapor depositing a metal electrode with a thickness of 100-200nm.
9. The use according to claim 8, characterized in that: The thickness of the hole transport layer is 10-100 nm, and the temperature of the heat treatment for making the hole transport layer is 60-100° C., and the time is 10-30 minutes.
10. The use according to claim 8, characterized in that: The transparent conductive substrate is tin oxide or nanowire; wherein the tin oxide is fluorine-doped tin oxide or indium-doped tin oxide; the nanowire is any one of activated carbon fiber fabric, silver nanowire and copper nanowire; the structure of the perovskite layer is specifically MAPbI3 or FAPbI3 or Cs 0.05 (FA 0.83 MA 0.17 ) 0.95 Pb(I 0.85 Br 0.15 )3 or Rb 0.05 Cs 0.05 MA 0.05 FA 0.85 Pb[I 0.95 Br 0.05 ]3; the electron transport layer material is one or more of fullerene derivatives and non-fullerene derivatives; the cathode interface modification material is bathocuproin, C 60 , titanium dioxide, and one or more of 2,4-diamino-6,7-diisopropylpteridine phosphate; the material of the metal electrode is any one of gold, silver, aluminum and copper.